Pengaruh Literasi Keuangan, Efikasi Diri, dan Love of Money Terhadap Minat Berwirausaha Mahasiswa Prodi Pendidikan Ekonomi STKIP PGRI Jombang - Yulia Effrisanti; Heru Totok Tri Wahono (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
The number of unemployed is still high and the low ratio of entrepreneurship in Indonesia, encourages the government to increase the entrepreneurship ratio index by creating young entrepreneurs. This study was to determine the influence of financial literacy, self-efficacy, and love of money on entrepreneurial interests. This study is quantitative research. The research population was 180 students of the economic education study program of STKIP PGRI Jombang. The research sample was 66 students. The research instrument uses a questionnaire. Data analysis techniques use t-tests, F-tests, and multiple linear regressions. The results showed that partially, financial literacy did not affect the interest in entrepreneurship. Meanwhile, self-efficacy and love of money partially affect the interest in entrepreneurship. Simultaneously, financial literacy, self-efficacy, and love of money affect the interest in entrepreneurship.